2019
DOI: 10.3390/met9091007
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Hydrogen Transport Behaviour in Boron-Manganese Steels Using Different Methods and Boundary Conditions

Abstract: Within the framework of the project "ELOBEV" (research of electrolytic coating systems for joining elements made of high-strength materials) funded by the Federal Ministry of Education and Research, a test methodology for the assessment of the danger of hydrogen-assisted and liquid metal-induced cracking for auxiliary joining elements is being developed. One working point of the project is the determination of the hydrogen transport behaviour in high-strength boron-manganese steels and their coating concepts. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Figure 3 b shows typical hydrogen permeation curves of a 22MnB5 PHS. [ 99 ] The sample thickness and charging current density were kept constant to reveal the effect of different pH values of the electrolyte on the permeation behavior. It was found that the pH values imposed significant changes on the effective diffusion coefficient and the subsurface hydrogen concentration.…”
Section: Hydrogen Ingress and Characterizationmentioning
confidence: 99%
“…Figure 3 b shows typical hydrogen permeation curves of a 22MnB5 PHS. [ 99 ] The sample thickness and charging current density were kept constant to reveal the effect of different pH values of the electrolyte on the permeation behavior. It was found that the pH values imposed significant changes on the effective diffusion coefficient and the subsurface hydrogen concentration.…”
Section: Hydrogen Ingress and Characterizationmentioning
confidence: 99%
“…Applications involve the analysis of "trapped" and "diffusible" hydrogen in steels [24,[27][28][29], hydrogen trapping [25] (see Figure 3), hydrogen-induced second phases, and hydrogen embrittlement mechanisms in Ti alloys [14,24] and hydrogen-storage materials [30]. TDS analysis, together with thermogravimetry, was also used to characterize Ti-H reference materials for the analysis of higher concentrations of hydrogen [31].…”
Section: Thermal Desorption Analysismentioning
confidence: 99%